The Effect of Transformational Leadership and Organizational Climate on Employee Performance Through Organizational Commitment as an Intervening Variable - Irwan Sani (IPM2KPE, 2024)
This research aims to explore the influence of transformational leadership and organizational climate on employee performance through organizational commitment. The method used is a quantitative descriptive method. The research results show that transformational leadership and organizational climate have a positive and significant influence on organizational performance, both directly and through organizational commitment. The conclusion is that the role of transformative leadership and a conducive organizational climate is important in improving employee performance through a high level of organizational commitment. Keywords: Employee Performance, Organizational Climate, Transformational Leadership, Organizational Commitment